Hepatitis C virus's next top models? - Paul, David; Bartenschlager, Ralf (Nature microbiology, 2016)
Advances in culturing hepatitis C virus have given hope for a universal cell culture system amenable to primary isolate replication. However, low replication efficiency needs to be overcome. The development of fully susceptible yet immunocompetent in vivo models would aid research towards a prophylactic vaccine.
Gesehen am 17.06.2020